Transforming Biology Education : The Need for Interactive Learning Media to Enhance the Experience of Eighth-Grade Students - Dea Putri Ramadhani; Mellisa Mellisa (Lombok Institute, 2024)
This study aims to identify the need for the use of learning media at SMPN 11 Pekanbaru. Learning media serve as tools to assist teachers in delivering material and facilitate students' understanding of the lessons. The research was conducted from November 13 to December 2024, utilizing survey and quantitative descriptive methods. The results from interviews and observations indicate that the current learning media are less engaging and varied, leading to difficulties for some students in comprehending the material. The instructional materials applied are still limited to textbooks and worksheets. According to the questionnaire, the impact indicator of using learning media received the highest score (82%), while the indicators for student difficulties and engagement received the lowest score (68%). The overall total score reached 74%, categorizing it as